Design with voids: how inverted urbanism can increase urban resilience. (3rd September 2018) - Roggema, Rob
ABSTRACT: In this paper ways in which currently fashionable eco-urbanism projects that are designed to increase the resilience of existing systems and practices contribute to a real transformation towards resilient cities, are explored. The small changes they promote do not often transform existing urban environments into genuinely more sustainable novel ones. Here a more radical approach is proposed, which maps the 'voids', the so far undefined design potentials extant within the urban fabric and uses this mapping as a starting point for the (re-)design of a city. The proposition of this article is that it is possible to invert the urban development process from its current focus on working solely with existing physical forms to manifest, and build on, its latent opportunities. Instead of looking at the tangible and visible fabric of the existing systems and designing sustainable add-ons to them, a process is promoted that exposes and analyses the potentials, and conversely the flaws, of the existing built environment to provide a new starting point for urban design. This re-ordering of the development priorities of a city has been developed to increase the long-term resilience of the mapped areas by also exposing vulnerabilities and compensating for them to enhance the health, safety and quality of life of residents within the spaces of current cities over time.